Prevalence and Factors Associated with Hypertension among Adolescents in Malaysia - JK, Liew; XP, Cheong; L, Law; WH, Teo; SS, Eng; CF, Ngim; A, Ramadas (IIUM Medical Journal Malaysia, 2019)
Introduction: Evidence has shown an increase in paediatric hypertension globally and this could give rise to increase prevalence of adult hypertension. The purpose of this paper was to determine the prevalence of hypertension among adolescents in Malaysia as well as the association between hypertension and lifestyle factors selected based on published literature. Methods: Adolescents aged 13-17 years old were selected randomly from two secondary schools to have their blood pressure measured. Their lifestyle information was obtained through completed bilingual questionnaires based on validated instruments, as well as anthropometry measurements. The relationship between hypertension and lifestyle factors was determined through statistical analysis. Results: A total of 273 students were included in the study with 120 (44%) males and 153 (56%) females. The prevalence of hypertension was 24.5% among the respondents with the highest being recorded among Malays (28.7%). Generally, hypertension was associated with an increased Body Mass Index (BMI) (AOR=4.053, 95%CI=1.677-9.795, p=0.002) and waist circumference (WC) (AOR=2.918, 95%CI=1.171-7.269, p=0.021) in all respondents. Similar associations were noted in females (BMI: AOR=7.707, 95%CI=2.043-29.072, p=0.003; WC: AOR=3.690, 95%CI=1.011-13.464, p=0.048) but not in males. Conclusion: Hypertension recorded high prevalence among Malaysian adolescents in our study. The strong association between elevated body weight, BMI and WC with hypertension may require further study to evaluate the need for screening